Exploring Student Motivation in Learning Creative Products and Entrepreneurship at a Vocational High School in Indonesia - Puspita, Zahra; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
Learning motivation refers to the internal drive that initiates and sustains students' engagement in the learning process. This study aims to explore the level of learning motivation among 11th-grade students in the Creative Products and Entrepreneurship course (locally known as PKK) at SMK Muhammadiyah 1 Semarang, Indonesia. A descriptive quantitative approach was employed, using a questionnaire based on Keller’s ARCS motivation model (Attention, Relevance, Confidence, Satisfaction). The sample consisted of 49 students selected through random sampling. Descriptive analysis revealed that students' overall learning motivation was in the high category, with an average score of 80.1 out of 100. Among the four ARCS components, Satisfaction received the highest mean score, while Attention was the lowest. These findings suggest that while students generally feel positive and satisfied with the learning experience, strategies to better capture and maintain their attention should be strengthened. The study highlights the importance of motivational design in vocational education to enhance student engagement and learning outcomes.